(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The Hănțilă method is a fixed-point method which treats nonlinearity by constructing a Picard-Banach sequence with assured convergence. Sometimes, the contraction factor of the operator building the iteration sequence is very close to the unit value and thus the convergence is rather slow. We propose and analyze several procedures for accelerating the calculation algorithm in case of utilizing the Hănțilă method for solving nonlinear three-phase circuits.